(3ehLR GdbGfhfs - (3GdbQTj, GHf GdfajS, YdGA GdOjf, Ydj Hf CHj GdMRe, J(B687 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3bO QJHJ gPG GdcJGH Ydi CQHYI afhf ; Gdaf GdChd aj bhGYO LRFj GdWH CYfj YdejI hYedjI Hbhd cdj, Gdaf GdKGfj aj GdCOhjI hGdCZPjI GdeaQOI hGdeQcHI , Gdaf GdKGdK aj GdCeQGV (B...s
(3BNQgG (B:s
.. (3cHO GdcrdH GdncpdH ojSbi deYVhVg ajDef ef GdaRY ef GdeGAhbO TgO HPdc LeGYI hbO YV cdlH cdH CQHYjf QLdG aCcd HYVge ef cHOg aGSJfca GdHGbj ef CcdgG aef CcdgG de jeJ (B...(3Jes
(3JHUQI GdYfhGf (B:s
(3aj GdWHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\270s
(3cTa GdXfhf (B2\1899s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs